2011
DOI: 10.1289/ehp.1002616
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinol-Binding Protein Concentrations and Thyroid Homeostasis with Nonoccupational Exposure to DDT

Abstract: BackgroundThe insecticide dichlorodiphenyltrichloroethane (DDT) has been used for malaria vector control in the northern and eastern parts of the Vhembe District of Limpopo Province, South Africa, since 1945. Bioaccumulation of DDT raises concern because it reportedly affects thyroid function.ObjectiveOur objective was to investigate the association between DDT uptake (as reflected in plasma concentrations) and thyroid homeostasis while considering related factors.MethodsWe compared dietary intake, serum retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It is especially the first-born infants that will be exposed to higher ΣDDT levels; therefore experiencing greater risk when compared with their sibs. Research conducted in the same region as Dididi identified DDT-associated effects on male urogenital parameters and reduction of retinol binding protein (Aneck-Hahn et al, 2007;De Jager et al, 2009;Bornman et al, 2010;Delport et al, 2011).…”
Section: Exposure and Riskmentioning
confidence: 99%
“…It is especially the first-born infants that will be exposed to higher ΣDDT levels; therefore experiencing greater risk when compared with their sibs. Research conducted in the same region as Dididi identified DDT-associated effects on male urogenital parameters and reduction of retinol binding protein (Aneck-Hahn et al, 2007;De Jager et al, 2009;Bornman et al, 2010;Delport et al, 2011).…”
Section: Exposure and Riskmentioning
confidence: 99%
“…Recent studies from South Africa found reduced retinol-binding protein and thyroid hormone concentration, urogenital malformations in newborn boys, and impaired semen quality, associated with non-occupational exposure to DDT (Aneck-Hahn et al, 2007;Bornman et al, 2010;Delport et al, 2011).…”
mentioning
confidence: 99%
“…Little is known about mechanisms of action of DDXs on vitamin A status. Delport et al (2011) showed that long-term DDT uptake reduced RBP concentrations in human blood.…”
Section: Relationships Between Ocps and Vitamin Amentioning
confidence: 99%
“…Studies on laboratory and wild animals generally report depleted hepatic and adipose tissue retinoid stores as well as increased levels in the kidneys (Zile, 1992;Håkansson et al, 1994;Hallgren et al, 2001;Nyman et al, 2003;Ellis-Hutchings et al, 2006;Mos et al, 2007;Nová k et al, 2008). In plasma, both an increase and a decrease of vitamin A levels have been observed, probably depending on the species, the physiological state and the concentrations at which the animals were exposed (Zile, 1992;Nyman et al, 2003;Nová k et al, 2008;Cesh et al, 2010;Delport et al, 2011).…”
Section: Introductionmentioning
confidence: 99%